Global Health Economics:Shaping Health Policy in Low- and Middle-Income Countries - Paul Revill (World Scientific Series in Global Health Economics and Public Policy, 2020)
This book contains a collection of works showcasing the latest research into global health economics conducted by leading experts in the field from the Centre for Health Economics (CHE) at the University of York and other partner research institutions. Each chapter focuses upon an important topic in global health economics and a number of separate research projects. The discussion delves into health care policy evaluation; economic evaluation; econometric and other analytic methods; health equity and universal health coverage; consideration of cost-effectiveness thresholds and opportunity costs in the health sector; health system challenges and possible solutions; and others. Case study examples from a variety of low- and middle-income countries (LMIC) settings are also showcased in the final part of this volume. The research presented seeks to contribute toward increasing understanding on how health policy can be enhanced to improve the welfare of LMIC populations. It is strongly recommended for public health policymakers and analysts in low- and middle-income country settings and those affiliated to international health organizations and donor organizations.